Low Alpha-Fetoprotein HCC and the Role of GGTP. Issue 4 (October 2014) - Carr, Brian I.; Guerra, Vito; Giannini, Edoardo G.; Farinati, Fabio; Ciccarese, Francesca; Rapaccini, Gian Ludovico; Di Marco, Maria; Benvegnù, Luisa; Zoli, Marco; Borzio, Franco; Caturelli, Eugenio; Chiaramonte, Maria; et al.
Background: HCC patients are heterogeneous in terms of both tumor and liver factors. Alpha-fetoprotein (AFP) is an important prognostic tumor marker for those patients with elevated AFP levels. Aims: To examine the differences in HCC patients with high or low AFP levels in blood and evaluate the prognostic parameters in low AFP patients. Methods: A cohort of 2, 440 HCC patients from 11 Italian medical centers was studied. AFP-positive patients were compared to AFP-negative ones, and the blood and tumor parameters of AFP-negative patients were examined. Results: Low blood AFP levels were found in 58% of the total cohort, in 64% of patients with small HCCs, and in 51% of patients with large HCCs. In patients with large tumors, platelet and gamma glutamyl transpeptidase (GGTP) levels, tumor multifocality and portal vein thrombosis (PVT) incidence were all greater than in patients with small tumors, regardless of AFP status. Patients with higher AFP levels had worse survival rates than those with low AFP in each tumor size group. In patients with small tumors, the elevated AFP was associated with significantly increased PVT and worse survival. In patients with large tumors, the elevated AFP was associated with significantly higher GGTP, ALKP, and bilirubin levels, as well as with increased PVT and multifocality, and worse survival. Low-AFP patients with high GGTP levels had worse survival than patients with low GGTP levels. Conclusion: Patients with low AFP were the majority in this cohort, and patients with elevated GGTP had worse prognosis than those with low GGTP. GGTP may be a useful tumor and prognosis marker in low-AFP patients. AFP-negative patients are important to identify due to their enhanced survival.